Pengaruh Iklim Psikologis terhadap Komitmen Afektif yang Berdampak pada OCB Karyawan di PT. Petrokimia Gresik - Jerry Marcellius Logahan; Harsya Rahman (Bina Nusantara University, 2015)
Seeing the considerably high increased in the growth of fertilizer industries in Indonesia, the company in the line business of fertilizer will have a lot of challenges and it needs to be handled in extra energy, especially the human resources of the company. The purpose of this study is to investigate the influence of psychological climate on affective commitment that impact on OCB (Organizational Citizenship Behavior) of the employees at PT. Petrokimia Gresik. Respondents in this study were the employees of PT. Petrokimia Gresik of 103 respondents. Data were analyzed by using analysis techniques of SEM -PLS (Partial Least Square). The results of this study indicate that there is an influence between employees’ psychological perceptions and organizational citizenship behavior of employees directly or indirectly through affective commitment. Advice that can be given to the company is to improve the psychological perceptions of the employees therefore it will increase the affective commitment that will give impact to the improvement of employees’OCB of PT. Petrokimia Gresik.